The content of the professional training of the teacher in Kazakhstan - Sholpan Kolumbayeva, Korlan Zhampeisova, Takir Balykbayev, Takir Balykbay, (Opción, 2019)
The aim of the study is to reveal and substantiate the national component of the content of pedagogical education and its influence on the development of the national consciousness of the future teacher. The leading approach to the study of this problem isunderstanding the essence of national ethnic, multicultural and intellectual education. The researchers identified pedagogical conditions that contribute to the effective implementation of the national component of vocational training in the educational process. The materials of the research are of practical value for updating the content of all levels of education and designing the national educational system.